FORMATION AND EVALUATION OF FINANCIAL ACTIVITIES OF A COMMERCIAL ENTERPRISE IN MODERN CONDITIONS - G. V. Goliguzova (Дискурс, 2017)
The purposes and types of financial activities of commercial enterprises in modern conditions, sources of formation of financial results, their evaluation on the basis of financial statements of commercial enterprises are considered.